Chronic venous ulcers: a review on treatment with fibrin sealant and prognostic advances using proteomic strategies - Fernandes Abbade, Luciana Patricia [UNESP]; Ferreira, Rui Seabra [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Barraviera, Benedito [UNESP] (Cevap-sao Paulo State Univ-unesp, 2020)
Venous ulcers are the main causes of chronic lower-limb ulcers. The healing difficulties encourage the research and development of new products in order to achieve better therapeutic results. Fibrin sealant is one of these alternatives. Besides being a validated scaffold and drug delivery system, it possesses excellent healing properties. This review covered the last 25 years of the literature and showed that the fibrin sealant is used in various clinical situations to promote the healing of different types of ulcers, especially chronic ones. These are mostly venous in origin and usually does not respond to conventional treatment. Commercially, only the homologous fibrin sealants obtained from human blood are available, which are highly efficient but very expensive. The heterologous fibrin sealant is a non-commercial experimental low-cost product and easily produced due to the abundance of raw material. The phase I/II clinical trial is already completed and showed that the product is safe and promisingly efficacious for the treatment of chronic venous ulcers. In addition, clinical proteomic strategies to assess disease prognosis have been increasingly used. By analyzing liquid samples from the wounds through proteomic strategies, it is possible to predict before treatment which ulcers will evolve favorably and which ones will be difficult to heal. This prognosis is only possible by evaluating the expression of isolated proteins in exudates and analysis using label-free strategies for shotgun. Multicentric clinical trials will be required to evaluate the efficacy of fibrin sealant to treat chronic ulcers, as well as to validate the proteomic strategies to assess prognosis.
Keywords: Biological dressings; Proteomics; Venous ulcers; Fibrin tissue adhesive; Biopolymers